Thalidomide has both anti-inflammatory and regulatory effects in Behcet's disease - DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (SPRINGER, 2008)
Thalidomide is shown to be an effective treatment for mucocutaneous symptoms of Behcet's disease (BD). In this study, the effects of thalidomide on peripheral blood mononuclear cells were investigated ex vivo. In an open prospective study, ten patients were given 200 mg/day thalidomide for 12 weeks and cluster of differentiation 4 (CD4), CD8, CD11a, CD11b, CD16, CD18, CD28, CD44, CD45RO, CD45RA, CD56, CD120a and gamma delta+ T cells were analysed with flow cytometry at 0, 3, 7, 30 and 90 days. Two patients were excluded from the analysis for attacks of uveitis within the first 2 weeks. At day 7, tumour necrosis factor-alpha (TNF-alpha) receptor+ (CD120a; 12% vs 5%), CD8/CD11b+ (12% vs 6%) and CD16/CD56+ (16% vs 9%) cells decreased in BD patients compared to day 0. On the other hand, CD4+CD45RO+ T cells (24% vs 34%) at day 30 and gamma delta+ T cells (11% vs 21%) at day 90 increased after treatment. These results suggest that thalidomide tends to decrease TNF-alpha receptor levels, CD8/CD11b+ T cells and natural killer cells in early treatment and increases CD4+CD45RO+ memory T and gamma delta+ T cells later in BD.
Keywords: Behcet's disease; T cells; thalidomide; T-CELLS; ACTIVATION; ALPHA; TNF